2017
DOI: 10.1177/1708538117735457
|View full text |Cite
|
Sign up to set email alerts
|

The associations of body composition and anthropometric measures with carotid intima-media thickness in obese and non-obese schoolchildren: A possible predictor for cardiovascular diseases

Abstract: Background Increased carotid intima-media thickness is one of the predictors of future cardiovascular diseases. However, it is still unknown which body composition parameter or anthropometric measure is the best predictor for carotid intima-media thickness change among children and young adolescents. Objective To investigate the associations of body composition and anthropometric measures with carotid intima-media thickness among a group of obese and normal bodyweight schoolchildren. Methods A total of 125 sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…13 It is a risk factor for the development of diseases such as diabetes, hypertension, coronary heart disease and some different types of cancer. [14][15][16][17][18][19][20][21][22][23][24][25] Obesity is related to mitochondrial metabolism. [26][27][28][29][30][31] The excess of fat in the tissues and the overweight aspect of it enhance the production of reactive oxygen species (ROS), which contribute to the origin and establishment of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…13 It is a risk factor for the development of diseases such as diabetes, hypertension, coronary heart disease and some different types of cancer. [14][15][16][17][18][19][20][21][22][23][24][25] Obesity is related to mitochondrial metabolism. [26][27][28][29][30][31] The excess of fat in the tissues and the overweight aspect of it enhance the production of reactive oxygen species (ROS), which contribute to the origin and establishment of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, FFM has been considered a significant determinant of BP (44,46), regional arterial stiffness (46), CCA IMT, and lumen area (35,47). As previously mentioned, these findings are in contradiction with previous results, which did not show significant associations between FFM and structural parameters (e.g., IMT) and cardiovascular risk (39,40,48). Our findings significantly differ from previously published data, which showed a stronger association between FMI and baBP rather than with FFMI (51).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, the Avon Longitudinal Study of Parents and Children study showed that elevated levels of FFM were associated with increases in cIMT independent of FM 25) . Several previous studies used absolute FM and BF% as an index of body fat [21][22][23][24][25] . However, the absolute FM is correlated with height.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the association between body composition and cIMT, two different body compositions should be considered. Many previous studies have mutually adjusted FM and FFM to consider body composition [21][22][23][24][25] . However, there is a correlation between FM and FFM because higher FFM is required to carry excess body fat.…”
Section: Anthropometrymentioning
confidence: 99%